CONTAINER FOR THE TRANSPORTATION AND CONSERVATION OF IMMUNOBIOLOGICALS - Soares, C. B.; Reis, M. N. E.; Takane, B.; Almeida, F. M. (Revista de Engenharia Térmica, 2008)
A container was developed for the transport and conservation of immunological products under low temperatures of between 2 and 8 º C, within a time span of 8 hours. The container is practical, simple and userfriendly, and can be used in places without electric power, and all these advantages are added of low operational costs. The container proposed aims at meeeting the demand of the Programa Nacional de Imunizações (PNI- the National Immunization Program), through Cold Chain, which sets the standards for all the procedures concerning conservation, handling, distribution and transport of the vaccine from the laboratory that produces it to the moment of inoculation. Innitially, the container was specifically developed for Vaccine for Inactive Influenza Virus against flu, which, according to a survey conducted with laboratories, is the most widely consumed, and whose conservation time span is also applicable to other immunobiologicals After the design and construction of the prototype, the container was exhaustively tested under different weather conditions. The results of the experiment are being exposed and discussed in this paper and the prototype lived up to the expectations of the reserachers in terms of the time spans and temperatures foreseen for the conservation of the vaccine selected.